An extension of the six-point circle theorem for a generalised Van Aubel configuration. Issue 567 (November 2022) - Pellegrinetti, Dario; de Villiers, Michael
Abstract : We deal with an extension of the six-point circle theorem for the quadrilateral [1] when the Van Aubel configuration is generalised as in [2] and [3]: similar parallelograms are constructed, all internally or all externally, on the sides of a given quadrilateral.